2003
DOI: 10.1002/syn.10194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acetylcholine levels on the binding of a SPECT nicotinic acetylcholine receptor ligand [123I]5‐I‐A‐85380

Abstract: Although in vitro theory indicates that ligand binding is sensitive to competition with neurotransmitters, only some imaging ligands have shown such competition in vivo. The purpose of this study was to determine whether increases in acetylcholine (ACh) levels induced by an acetylcholinesterase inhibitor, physostigmine, inhibit in vivo binding of [(123)I]5-iodo-3-(2(S)-2-azetidinyl-methoxy) pyridine (5-I-A-85380), a single photon emission computed tomography ligand for the high-affinity type nicotinic ACh rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 40 publications
(35 reference statements)
3
25
1
Order By: Relevance
“…Although a finding of no sex difference in b 2 -nAChR availability in nonsmokers does not preclude a sex difference in b 2 -nAChR availability in smokers, it does raise the question of whether availability of b 2 -nAChRs is involved in the sex differences in tobacco-smoking behavior, such as differences in quitting smoking and in response to nicotine replacement therapy. Although 123 I-5-IA SPECT measures the availability of b 2 -nAChR, this measure may be confounded by occupancy of the receptor by endogenous acetylcholine (46). However, no reports of sex differences in endogenous acetylcholine levels could be found, and plasma acetylcholine does not vary in women with gonadal hormone levels (47).…”
Section: The Effect Of Sex On B 2 -Nachr Availabilitymentioning
confidence: 99%
“…Although a finding of no sex difference in b 2 -nAChR availability in nonsmokers does not preclude a sex difference in b 2 -nAChR availability in smokers, it does raise the question of whether availability of b 2 -nAChRs is involved in the sex differences in tobacco-smoking behavior, such as differences in quitting smoking and in response to nicotine replacement therapy. Although 123 I-5-IA SPECT measures the availability of b 2 -nAChR, this measure may be confounded by occupancy of the receptor by endogenous acetylcholine (46). However, no reports of sex differences in endogenous acetylcholine levels could be found, and plasma acetylcholine does not vary in women with gonadal hormone levels (47).…”
Section: The Effect Of Sex On B 2 -Nachr Availabilitymentioning
confidence: 99%
“…In vivo studies in both the baboon and human have demonstrated the potential usefulness of the ligand in the investigation of nAChRs (20,22). Similar to 2-[ 18 F]F-A-85380, compounds that can increase endogenous levels of acetylcholine, such as physostigmine, can effectively compete with [ 123 I]5-iodo-A-85380 for binding (19).…”
Section: -Iodo-a-85380mentioning
confidence: 99%
“…123 I]5-IA binding patterns (Fujita et al, 2003a). ABT-089 has been shown to improve behavioral performance across a range of cognitive domains in animals (Decker et al, 1997) but has demonstrated a mixed picture of ABT-089 (mg/kg, iv) at ASPET Journals on May 9, 2018 jpet.aspetjournals.org efficacy in humans (Wilens et al, 2006;Bain et al, 2009;Gault et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…123 I]5-IA seems to predominantly label the ␣ 4 ␤ 2 * subtype and that radioligand uptake can be displaced by endogenous acetylcholine as well as by nicotine and cytisine (Fujita et al, 2003a).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation